Target tracking with sensor navigation using coupled RSS and AOA measurements - Tomic, Slavisa (2018)
The authors would like to thank the editor and the anonymous reviewers for their valuable comments and suggestions which improved the quality of the paper. This work was partially supported by Fundacao para a Ciencia e a Tecnologia under Project PEst-OE/EEI/UI0066/2014, Project UID/EEA/50008/2013, Project UID/EEA/50009/2013, and Program Investigador FCT under Grant IF/00325/2015.